Utilization of modern educational technologies in the exploring of the history of craftsmanship - Sultankhojayev N; Shodiyeva D. A; Saxobiddinova F. (Zien Journals, 2022)
This feature provides reference on the importance of modern educational technologies in the exploring of the history of handicrafts in the field of technology
Keywords: Geometric patterns; Islamic ornaments; birds and animals; symbols